Chemotherapy-induced neutropenia and its determinants in patients with solid malignancies: A prospective observational study - Whitney Joseph J; Arumugam V (Asian Journal of Medical Sciences, 2025)
Background: Chemotherapy-induced neutropenia (CIN) is a significant dose-limiting toxicity of chemotherapy that can lead to severe infection and treatment disruption. Febrile neutropenia (FN) has an in-hospital mortality rate of 2–7% in adults with solid tumors. Aims and Objectives: This study evaluated the incidence, risk factors, and outcomes of CIN and FN in patients with solid malignancies in India. Materials and Methods: In this hospital-based prospective observational study conducted at Tirunelveli Medical College Hospital, 1,252 adult patients with solid tumors underwent chemotherapy over a 12-month period. Among these patients, 142 developed CIN and were included in the analysis. Demographic data, cancer stage, nutritional status, laboratory parameters, and radiotherapy and chemotherapy histories were recorded. CIN and FN were defined according to the common terminology criteria for adverse events v5.0. Patients were monitored for neutropenia and FN. Chemotherapy modifications, infection rates, and mortality were also recorded. Risk factor associations were analyzed using Chi-square and logistic regression analyses. Results: Among 142 patients (66.2% women), severe neutropenia (grade 3–4) occurred in 37.3% of patients, and FN occurred in 2.2% of patients, mostly during the initial chemotherapy cycle. Independent CIN risk factors included age >60 years (odds ratio [OR]: 2.21, P=0.043), male sex (OR: 2.93, P=0.005), underweight body mass index (OR: 2.35, P=0.086), smoking (OR: 3.54, P=0.003), comorbidities (OR: 3.08, P=0.02). Prophylactic granulocyte colony-stimulating factor (G-CSF) significantly lowered FN incidence (13.2% vs. 28.8%, P=0.038). The clinical consequences included dose delays (18.3%), reductions (17.6%), FN-related hospitalizations, and FN-related mortality (4.9%), predominantly in elderly patients. Conclusion: CIN and FN significantly affected the chemotherapy outcomes. Older age, malnutrition, comorbidities, and aggressive regimens increase the risk of developing this disease. Nutritional assessment and selective prophylactic G-CSF administration are critical for optimizing cancer care outcomes in resource-limited settings.